The Influence Of Earnings Per Share, Return On Equity, Return On Assets, And Net Profit Margin On Financial Distress In The Consumer Cyclicals Sector On The Indonesian Stock Exchange - Rizki Ary Mujianto; Dedi Hariyanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to determine the effect of EPS, ROE, ROA, and NPM on Financial Distress in the consumer Cyclicals sector for the 2020-2022 period. The population used in this research is the cyclical consumer sector on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. This type of research is quantitative. Using secondary data and purposive sampling techniques using SPSS 24. The research results show that EPS, ROE, ROA and NPM simultaneously do not have a significant influence on financial distress in cyclical consumer deposits on the Indonesia Stock Exchange (BEI) for the 2020-2022 period.